The Study of Workpiece Temperature During Machining in Dry Milling Stainless Steel - เบ้าวรรณ, ปรเมศวร์; สายแก้ว, ชาญณรงค์ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
Milling is one of the most important machining processes that can be developed for more effective cutting performance to avoid use of coolants and maintain environmental friendliness. Stainless steel is widely known as a hard-to-cut material due to its high ductility, strength and low thermal conductivity. The cutting temperature is high which causes a built-up edge on the cutting tool. A commonly used solution to this problem is to apply the coolant which has a harmful effect on workers’ health. Therefore, this research aimed to study the relationship between cutting temperature of workpiece and shapes of end mill as well as coating material for higher efficiency and environmental friendliness. The results showed that the end mill with a 60-degree helix angle coated with TiAlN was the best one that could prevent the wear of the end mill’s cutting edge and the increase in cutting temperature since the higher cutting temperature did not only stem from the wider cutting edge, but also the chipping wear.